Effects of feeding high protein or conventional canola meal on dry cured and conventionally cured bacon. (May 2015) - Little, K.L.; Bohrer, B.M.; Stein, H.H.; Boler, D.D.
Abstract: Objectives were to compare belly, bacon processing, bacon slice, and sensory characteristics from pigs fed high protein canola meal (CM-HP) or conventional canola meal (CM-CV). Soybean meal was replaced with 0 (control), 33, 66, or 100% of both types of canola meal. Left side bellies from 70 carcasses were randomly assigned to conventional or dry cure treatment and matching right side bellies were assigned the opposite treatment. Secondary objectives were to test the existence of bilateral symmetry on fresh belly characteristics and fatty acid profiles of right and left side bellies originating from the same carcass. Bellies from pigs fed CM-HP were slightly lighter and thinner than bellies from pigs fed CM-CV, yet bacon processing, bacon slice, and sensory characteristics were unaffected by dietary treatment and did not differ from the control. Furthermore, testing the existence of bilateral symmetry on fresh belly characteristics revealed that bellies originating from the right side of the carcasses were slightly ( P  ≤ 0.05) wider, thicker, heavier and firmer than bellies from the left side of the carcass. Highlights: We evaluated bilateral symmetry of fresh bellies used for bacon production. We compared bacon processing characteristics between two types of canola meal. There were no differences in bacon processing between the two varieties of canola meal. There were no sensory differences between the two varieties of canola meal. Bilateral symmetry must be considered when designing bacon experiments.